Cost-effective treatment modalities for reducing morbidity associated with chronic kidney disease. (April 2015) - Ferguson, Thomas W; Tangri, Navdeep; Rigatto, Claudio; Komenda, Paul
Abstract : Chronic kidney disease (CKD) is a worldwide health problem with increasing prevalence and incidence. Guidelines suggest that early referral to a nephrologist to manage advanced stage (4+) patients with CKD is an effective treatment strategy, with earlier stage patients best managed through primary care physicians. Should patients with CKD progress to total kidney failure, several therapies are available that vary widely in costs. Kidney transplantation offers the lowest costs and highest quality of life, followed in ascending order of costs by peritoneal dialysis, home hemodialysis and facility-based hemodialysis. Earlier detection of CKD may prevent progression to kidney failure, and accurate risk prediction of end-stage kidney failure may improve clinical planning, outcomes and resource allocation.